Analysis of sleep quality in cancer patients undergoing teletherapy (Brazilian Journal of Health Research, 2022)
Introduction: Cancer treatments offer a high level of success and have evolved considerably in recent times. However, cancer patients suffer from a high probability of developing adverse effects of therapies, such as changes in sleep quality. Objectives: To analyze the sleep quality of cancer patients undergoing teletherapy. Methods: Descriptive, inferential, cross-sectional and quantitative study. Cancer patients undergoing teletherapy at Hospital Santa Águeda, from September to December 2020, in Caruaru city- Pernambuco state, Brazil, were evaluated. Relevant to be aware of the obtaining of sociodemographic, clinical and lifestyle information. As an evaluative and validated instrument, the Pittsburgh sleep quality index was a significant tool in the form of an interview. For descriptive analyses, the probability distribution was also an important choice and, the chi-square test, for inferential ones, considering a significance level of p
Keywords: Medical Oncology; Sleep; Sleep disorder; Radioisotope Teletherapy